Impact of transversus abdominis plane block plus intravenous lidocaine on rapid recovery after bariatric surgery - Wang, Xin; Zhang, Yawen; Guo, Qiongmei; Wang, Li; Zhang, Jin; Yang, Zhenheng; Sun, Yuan (Frontiers in Medicine, 2025)
AimThe study aimed to explore the impact of transversus abdominis plane block (TAPB) combined with intravenous lidocaine on rapid recovery after bariatric surgery.MethodsA total of 80 patients who underwent elective bariatric surgery from October 2022 to October 2023 were selected as study participants and divided into a control group (CG) and a study group (SG). The CG received ultrasound-guided TAPB with ropivacaine, while the SG received ultrasound-guided TAPB with ropivacaine plus intravenous lidocaine. The two groups were compared in terms of total doses of propofol, remifentanil, and sufentanil used; pain intensity; intraoperative conditions; levels of inflammatory factors; additional use of postoperative analgesics; incidence of adverse reactions; and postoperative recovery time.ResultsCompared to the CG, the SG showed significant reductions in the total intraoperative doses of propofol, remifentanil, and sufentanil (p < 0.05). In addition, the SG had lower visual analog scale (VAS) scores at rest and during coughing at 12, 24, and 48 h postoperatively (p < 0.05), as well as lower heart rate (HR) and mean arterial pressure (MAP) values at time points T1–T3 (p < 0.05). On the first day after surgery, the levels of tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) in the SG were significantly lower than those in the CG (p < 0.05), and the SG also required less additional use of postoperative analgesics (p < 0.05). Furthermore, the SG exhibited a shorter time to first flatus, first defecation, and first ambulation, as well as a shorter length of hospital stay compared to the CG (all p < 0.05).ConclusionTAPB combined with intravenous lidocaine may provide effective postoperative analgesia for patients after bariatric surgery and may accelerate their rapid recovery.